Geometric morphologic variation of Dalbergia Hupeana Hance leaves and its response to different spatial structures - Deng, Nan; Song, Qingan; Tian, Yuxin (Bangladesh Journal of Botany, 2025)
This study was envisaged to reveal the variations in leaf shape of Dalbergia hupeana and its adaptation to the forest competition. Four different pure Masson pine sample plots were set, and the spatial structure of each plot was calculated; the leaves of D. hupeana from different positions were collected, and the outline reconstruction of leaves was performed using the Fourier/wavelet method. The results indicated that D. hupeana leaves in different plots showed a wide variation. The leaf area, length, width, perimeter, roundness, circularity, form factor, and rectangularity exhibited significant differences among the plots. Discriminant analysis showed that both the Wavelet and Fourier analyses could effectively separate different plots with good accuracy. The forest matrix crowding index, Diameter correlation index, DBH dominance, and Hegyi index were the key spatial indices that affected the leaf morphological variation. The study preliminarily investigated the effects of tree competition on functional traits of leaves, which can provide valuable information in forest management. Bangladesh J. Bot. 54(2): 325-335, 2025 (June)